Covid-19: An Update on Clinical Features, Diagnosis, and Treatment Strategies - Alhkbany, Manan A. (Coronaviruses, 2021)
The coronavirus disease 2019 (COVID-2019) has emerged as a new public health crisis, with the WHO officially declaring it as a pandemic on 30 January 2020. In December 2019, the virus was reported to be transmitted to humans through an unknown intermediary animal in Wuhan, Hubei province, China. As of 18 May 2020, there were 4,730,968 reported cases of Covid-19, with 315,488 deaths. Direct contact among individuals is the most common transmission method, primarily through droplets released during coughing or sneezing. The incubation period of the virus oscillates between 2 to 14 days. The commonly reported symptoms include fatigue, sore throat, cough, and fever. Most of the people are asymptomatic or show mild symptoms. The elderly and people with comorbidities show severe symptoms. The disease is diagnosed by using the real- time reverse transcription-polymerase chain reaction (RT-PCR) testing method. A blood test is also used to detect the antibodies to the virus, which are usually released after infection. The typical laboratory findings indicate elevated C-reactive proteins (CRP) with normal or low white blood cell counts; the chest CT scan demonstrates ground-glass opacities (GGO) and bilateral pneumonia in most patients. Supportive treatment is available, and research on the right treatment using existing drugs is ongoing. Several pharmaceutical companies and research institutions are focusing on the development of a vaccine. The review summarizes and provides an update on the pathogenesis, diagnosis, and treatment strategies in the management of Covid-19.
Keywords: severe acute respiratory syndrome